2018
DOI: 10.15406/ppij.2018.06.00211
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic intoxication by organophosphate insecticides on the parameters of innate and adaptive immunity and realization of the cholinergic anti-inflammatory pathway

Abstract: The effect of chronic intoxication by organophosphate insecticides on the parameters of innate and adaptive immunity and realization of the cholinergic anti-inflammatory pathway

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Humans exposed to occupational OPs are more prone to respiratory tract infections [ 37 ], so it may be that patients who ingest and aspirate OP + GJ are more prone to aspiration pneumonia than normal ICU patients, explaining in part the increased mortality in intubated OP-poisoned patients secondary to OP self-poisoning. The role of the cholinergic anti-inflammatory pathway [ 38 ] in suppressing inflammation due to OP insecticide-induced cholinergic overstimulation requires further investigation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Humans exposed to occupational OPs are more prone to respiratory tract infections [ 37 ], so it may be that patients who ingest and aspirate OP + GJ are more prone to aspiration pneumonia than normal ICU patients, explaining in part the increased mortality in intubated OP-poisoned patients secondary to OP self-poisoning. The role of the cholinergic anti-inflammatory pathway [ 38 ] in suppressing inflammation due to OP insecticide-induced cholinergic overstimulation requires further investigation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil function in 40 workers occupationally exposed to OP pesticides was disrupted to some extent ( Queiroz et al, 1999 ). Zabrodskii (2018) found that, chronic intoxication of rats with malathion and parathion methyl (0.01 LD 50 daily, for 30 days) significantly reduces the phagocytic-metabolic activity of neutrophils and NK cells. Li et al (2020b) have reported that, Triphenyl phosphate and Tris (2-butoxyethyl) phosphate partially attenuate the adhesion and phagocytic potential of the THP-1 mφs.…”
Section: Op-induced Immunotoxicitymentioning
confidence: 94%
“… Abou-Zeid et al, 2018 Malathion and Parathion methyl 0.01 LD 50 daily (815±28mg/kg malathion; 25.3±2.6mg/kg parathion methyl); 30 days Albino rats Reduced activity of neutrophils and NK cells; impaired antibody-dependent cellular cytotoxicity. Zabrodskii , 2018 Diazinon 10mg/kg; 30 days Male albino rats Reduced population of lymphocytes and monocytes; sub-optimum level of total serum immunoglobulin titer and hemagglutination; declined blood mononuclear cell proliferation, phagocytic index and blood T-cell subtypes (CD4 + and CD8 + ). Hassouna et al, 2015 Chlorpyrifos and Profenofos Chlorpyrifos: 6.75 mg/kg b.w.…”
Section: Op-induced Immunotoxicitymentioning
confidence: 99%
“…In addition, the effect of different OPs on cell populations has been described. In this regard, decreased antibody-dependent activity of neutrophils and NK cells was observed in rats after exposure to malathion and parathion [ 115 ]. Similarly, the effect of diazinon was studied in albino rats, which decreased the proliferation of blood mononuclear cells and blood T-cell subtypes (CD4+ and CD8+), as well as the reduction of total serum immunoglobulin and hemagglutination titers [ 116 ].…”
Section: Op-mediated Modulation Of the Immune Responsementioning
confidence: 99%
“…In addition, the function of the phagocytic-monocytic system after chronic poisoning of OPs compounds decreases, which is manifested by a reduction in the blood concentration of proinflammatory cytokines TNF-α, IL-1β, and IL-6. Further, chronic intoxication with OPs leads to the realization of the cholinergic anti-inflammatory pathway [ 115 ]. In human CD4+ T cells exposed to diethyl dithiophosphate (DEDTP), reduced T-cell proliferation and intracellular secretion of IL-2, IL-10, and IFN-γ were observed [ 19 ].…”
Section: Op-mediated Modulation Of the Immune Responsementioning
confidence: 99%